Audit Internal Dan Efektivitas Pengendalian Intern Penjualan Di PT Garuda Food Putra Putri Tbk - Dika Candra Laili,; Khansa Tsabita Wijaya, (Jurnal Mutiara Ilmu Akuntansi, 2024)
Internal Auditors who are not directly involved in operational activities can, therefore, assess all activities. Internal Auditors also provides objective information regarding sales data that will be the basis for management decision making. The purpose of this study is to: determine whether the internal audit on sales activities conducted by the company has been done adequately; determine whether the internal control over sales has been implemented effectively; and determine the role of internal audit in supporting the effectiveness of internal control sales. The authors perform hypothesis testing by doing descriptive analysis and statistical analysis. Based on the results, the effectiveness of internal control can be explained by the Internal Audit role of 63.2%.